Supporting multi-level quality of services in data broadcast systems. (2015) - Lv, Jingsong; Lee, Victor C.S.; Li, Minming; Chen, Enhong
In many large-scale applications such as intelligent transportation systems (ITS), internet of things (IoT) will play a leading role to fuse the physical world and information space connected by mobile communication networks. Within these applications, data broadcasting is a core component for disseminating information to a large population of mobile clients. Although scheduling in data broadcast systems has been widely studied, little attention has been paid to the quality of service (QoS) issue, which is crucial to any information dissemination application. To support different levels of QoS, data items could be allocated to multiple logical channels with speeds commensurate with respective QoS levels. An online EDF (Earliest Deadline First)-based dispatcher is devised to dispatch data items scheduled in the multi-channel allocation to the single physical channel in data broadcast systems. We prove that no data item dispatched by the dispatcher will be delayed with respect to their subscribed QoS levels.